Special issue: 30 years of ICT and learning in education – major changes and challenges - Haugsbakk, Geir (Seminar.net, 2020)
The expectations of the possible impact of ICT on teaching and learning have been huge, and over the past few decades ICT has played an increasingly important part in education all over the world. Educational technology has been high on the political agenda, significant achievements have been noted and a whole range of actors have benefited from public funding for a variety of projects trying to make use of educational technologies in education. Less attention has been given to research in field, and critical reflections have been rare. A main aim of this special issue of Seminar.net is to focus major changes and challenges after (more than) thirty years of ICT and learning in education. Research identifying dominating ideas within the field of educational technology has been highlighted, but also the leading providers of ideas and strategies and the extent to which these ideas have resulted in consistent and convincing arguments. This has involved efforts to identify the key actors and networks and what can be regarded as the main activities and milestones. Moreover, this is about how successful the policies of ICT in education have been and trying to provide a platform for future policies. This is a rather complex matter, and such analysis and reflections have usually not been given priority in the field of educational technology. Similar aims formed the basis for an international research seminar in Lillehammer in January 2018, and the initial initiative to opt for a special issue was put forward during this seminar. The plans were strongly supported by the 2018 network meeting of network 6 (Open Learning: Media, Environments and Cultures[1]) in the European Educational Research Association. The Lillehammer seminar included thirteen researchers from five different countries: Australia, USA, Germany, Scotland, Sweden and Norway. All five contributions published as research articles in the present issue of Seminar.net are based on presentations given at the seminar. The framework for the discussions was established by two keynote talks given by Neil Selwyn, Monash University, and Norm Friesen, Boise State University. Norm Friesen’s presentation has been developed into a research article included in this special issue. Neil Selwyns gave a thought-provoking keynote that so far still exists in a not published written draft. In this he briefly summarises some of his main viewpoints and arguments. Selwyn acknowledges that there are several interesting and insightful studies of education and technology, but he adds that the overall quality of research in this area has been understandably criticised over the past thirty years. He reflects on the need for education researchers to take care to resist falling into the trap of reaching polarized portrayals of digital technology in terms of either being good/bad, beneficial/harmful or descending into confirmatory roles of providing bland accounts of “what works and why”. He argues that we need research for the 2020s that explores the complexities, contradictions and inherently political nature of education and technology. According to Selwyn, we have to make sure that our work offers unbiased and disinterested alternatives to those who think that they already know the answers. This implies “to go beyond the digital”, and that the contemporary digital education might be better understood as entanglements of humanity, materiality and digitality. (This presentation is based on Selwyns not published draft.) In his article in this special issue, Norm Friesen begins by examining book culture - one which provides long-familiar demarcations of knowledge and ignorance, development and depravation that are starting to lose their force. Appealing to the notion of the longue durée, he then turns to the history and contemporaneity of the book in educational discourse. He considers what the changing educational significance of the book can tell us about change in education itself, and what this ongoing change might mean for us today. Friesen’s approach is based on seeing the book as an epochally and epistemologically foundational medium. The book’s physical nature, its typical contents, the habits and practices associated with its use, and the way that these are acquired, can thus be said to together constitute the paradigm for knowing. Rachel Shanks presents a reflective and reflexive account in relation to seven educational technology projects carried out, over the last ten years, in Scotland. The analysis is based on her own framework developed to understand why some of these educational technology projects were successful and why others were not. Her ambition is that this work can help to link practice back to research as well as indicating a way for lessons to be learnt in future educational technology projects. Shanks’ underlying assumption is that educational technology the last thirty years has not impacted the delivery of education that might have been predicted for it. Part of the lack of impact may relate to the introduction of new technologies through one-off educational technology projects which lack permanence and effective evaluation. Rensfeldt and Player-Koro examines major Swedish school digitalization curriculum reforms going back to the late 1960s. They examine how digitalization reforms are constituted discursively and materially in struggles over curricular knowledge content, preferred citizenship roles, and infrastructural investments and especially by relating curricular reforms to governance transformations. One recurrent strategy of reform is what they call the back to the future argument, where curricula address an ideal citizenship of future societies, politically used to support change. This movement has taken place partly through central, state-led or new monopolized technology governance and infrastructures and partly through decentralized forms of governing. Bjørgen and Fritze aim to shed light on the media practices considered by students as important and how their experiences correspond with the teachers' academic use of media. High expectations form the basis of their analysis, as exemplified by statements of the Norwegian Educational Quality Reform two decades ago. This implies that student-activating teaching methods by the use of digital technology might increase the scope of student-active learning. The authors have focused on a bachelor's course in Media Education, and based on data from interviews, a survey and activity logs in the students’ learning platform they conclude that students seem to prefer to study effectively, at the expense of activating teaching methods and of being active producers of learning. And although students are expected to be digitally competent, it should not be assumed that they master technology as expected in higher education. Haugsbakk and Nordkvelle address what they consider to be dominant arguments, discourses and issues related to the hegemonization of meaning formation in the field of educational technology. Their line of reasoning is based primarily on a case study of the leading journal in the field in Norway over the last fifteen years. Placing the journal’s policy at the forefront, the focus of their analysis is on the editorials. The main findings, based on issues of the journal over the first ten years, are that the editorials are in keeping with what may be regarded as the political priorities and the prevailing political discourses in the field. They contain relatively few, if any, critical perspectives and scant reference is made to the research articles and research area the journal claims to serve. [1] https://eera-ecer.de/networks/6-open-learning-media-environments-and-cultures/